Clinical Studies On Chemical Immobilization Of Stray Bulls For Capture And Rehabilitation: Part Ii - Joshi, D.O.; Tank, P.H.; Dhami, M.A.; Maradia, M.G.; Dhami, A.J.; Patel , P.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Three selected anesthetic protocols of chemical immobilization found suitable in preliminary Part I study were applied on 203 stray bulls in this study for their capture in the city area. This included intramuscular injections of Xylazine alone @ 0.2 mg/kg b. wt. in Group I (n=66); Xylazine and Ketamine (XK) mixture @ 1.0 ml/bull (55.55 mg Xylazine and 44.44 mg Ketamine) in Group II (n=48), and @ 1.5 ml/bull (83.32 mg Xylazine and 66.66 mg Ketamine) in Group III (n=89). Group I bulls showed complications like tachycardia, either hyperthermia or hypothermia and prolonged sedation time. Despite completely sedated Group III bulls could move or kick, showed rumen stasis and tympany. After capture, total 147 (60.49%) bulls were castrated to prevent indiscriminate breeding. In this Part II study, results found were almost similar to preliminary Part I study, except that the mean per cent of injury, darting failure, redosing and chase time (min) were decreased from 2.50, 70.00, 20.00 and 14.42±0.03 in Part I to 1.48, 26.60, 10.84 and 13.13±0.01, respectively in Part II study, due to increased experience with darting process. Results of present study indicated that Xylazine @ 0.2 mg/kg b.wt. or XK mixture @ 1.0-1.5 ml (55.55-83.32 mg Xylazine and 44.44-66.66 mg Ketamine) per bull for chemical immobilization at an approximately 4 meters darting distance is effective for its uneventful capture and hence is recommended for use to capture and rehabilitate stray bulls from the city areas.